THE RELATIONSHIP OF EGYPT WITH ARAB COUNTRIES OF 1980-1990th YEAR’S - Zhanataeva, К B (Journal of Oriental Studies, 2016)
This article regards the relationship of Egypt with other Arab countries. Rapprochement of the Arab Countries after the termination of the contract of Camp David, it has become an important area of foreign policy of Egypt.